Hepatocyte FoxO1 depletion exacerbates hepatic inflammation in MASH by targeting cystathionine γ-lyase - Chen, Hui-Ting; Huang, Chen; Chen, Jia-Wei; Yang, Si-Qi; Cheng, Jie-Min; Li, Yong-Qiang; Chen, Han-Qing; Zhou, Yong-Jian (Scientific reports, 2025)
The transcription factor Forkhead box protein O1 (FoxO1) is a well-established regulator of glucose and lipid metabolism, yet its role in metabolic dysfunction-associated steatohepatitis (MASH) pathogenesis remains debated. This study investigates hepatocyte-specific FoxO1 mechanisms driving hepatic inflammation in MASH. Using hepatocyte-specific FoxO1-knockout (KO) mice fed a methionine-choline-deficient diet and LPS-treated FoxO1-KO cells, we demonstrated that FoxO1 depletion exacerbates hepatic inflammation, ballooning degeneration, and upregulates TNF-α, CXCL8, and CXCL2 in vivo and in vitro. Transcriptomic analysis revealed that FoxO1 deficiency upregulated pro-inflammatory pathways while suppressing cysteine/methionine metabolism, with a notable reduction in cystathionine γ-lyase (CTH) expression. Luciferase assays confirmed that FoxO1 directly binds the CTH promoter. In MASH mice, reduced CTH levels correlated with elevated TNF-α/CXCL8. Pharmacological CTH inhibition via β-cyano-L-Alanine (BCA) amplified LPS-induced inflammation in THLE-2 cells, while CTH overexpression rescued inflammatory responses in FoxO1-deficient hepatocytes. Our findings unveil FoxO1 as a transcriptional activator of CTH, coupling metabolic adaptation to inflammatory regulation in MASH, and propose the FoxO1-CTH axis as a therapeutic target for inflammatory liver disease.